An Analysis of Students’ Reading Comprehension in Narrative Text at Second Grade At SMAN 1 Talamau - Yessy Marzona; Muhammad Ikhsan (Fakultas Sastra Universitas Ekasakti, 2019)
This research was conducted based on the problems found during the teaching and learning process in class IX IPS 1 of SMAN 1 Talamau, specifically about students' understanding of narrative text. The problem found is that students cannot determine the main ideas and topics in narrative text, understand the meaning of words, understand implied information, and understand the general structure and features of language in narrative texts.This research is included in quantitative descriptive research. The population in this study were students of class IX SMAN 1 Talamau, amounting to 159 people, divided into 4 classes. While this sample is class X8 of SMAN 8 Padang. The instrument used was an objective test. Data from students' objective tests are analyzed based on indicators and then interpreted and become research findings.Based on the results of the study showed that students of class IX IPS 1 SMAN 1 Talamau: 1. The ability to write students in determining the main ideas and topics in the narrative text showed at the intermediate level of 14 people out of 23 students (60,875%). 2. The ability to understand the meaning of words in the narrative text shows at the intermediate level that is 15 people out of 23 students (65.22%). 3. The ability to understand the information implicit in the narrative text shows that at the intermediate level, there are 14 out of 23 students (60.87%). 4. The ability to understand the general structure and language features of narrative texts shows that at the intermediate level, there are 16 students out of 23 students (69.57).From the results of the above research, it can be concluded that students still experience many difficulties in understanding a text, especially in narrative texts in accordance with applicable rules. Furthermore, based on the results of this study teachers are expected to be able to provide better teaching techniques and students can do more exercises to improve students' reading comprehension abilities.